Strategies for Enhancing Vaccine-Induced CTL Antitumor Immune Responses - Yong, Xin (Hindawi Publishing Corporation, 2012)
Vaccine-induced cytotoxic T lymphocytes (CTLs) play a critical role in adaptive immunity against cancers. An important goal of current vaccine research is to induce durable and long-lasting functional CTLs that can mediate cytotoxic effects on tumor cells. To attain this goal, there are four distinct steps that must be achieved. To initiate a vaccine-induced CTL antitumor immune response, dendritic cells (DCs) must capture antigens derived from exogenous tumor vaccines in vivo or autologous DCs directly loaded in vitro with tumor antigens must be injected. Next, tumor-antigen-loaded DCs must activate CTLs in lymphoid organs. Subsequently, activated CTLs must enter the tumor microenvironment to perform their functions, at which point a variety of negative regulatory signals suppress the immune response. Finally, CTL-mediated cytotoxic effects must overcome the tolerance induced by tumor cells. Each step is a complex process that may be impeded in many ways. However, if these steps happen under appropriate regulation, the vaccine-induced CTL antitumor immune response will be more successful. For this reason, we should gain a better understanding of the basic mechanisms that govern the immune response. This paper, based on the steps necessary to induce an immune response, discusses current strategies for enhancing vaccine-induced CTL antitumor immune responses.